Poetics of irrational in the novel "The Lost Man" by M. Pavlyk (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
On the material of Pavlik's little known novel «Lost Man» an attempt to justify its polyaesthetical nature by referring to the irrational part of the novel content is made. The following irrational elements are identified: the state of agony, dream, ap-parition, with which the author forms a pattern of the main character behavior. Poeti-cal features of character and structure formation of the text are considered: gradua-tion, reflectivity, symbolism, oxymoron, composition ring. The genre form of the novel is defined as apparition novel.
Keywords: apparition novel; irrational; poetics